KARAKTERISTIK DAN SKRINING FITOKIMIA EKSTRAK ETANOL 70% BATANG KEPUH (Sterculia foetida L.) - Cahyani, N. P. S. E.; Susiarni, J.; Dewi, K. C.S.; Melyandari, N. L.P.; Putra, K. W.A.; Swastini, D. A. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019DO - 10.24843/JCHEM.2019.v13.i01.p04, 2019)
Kepuh (Sterculia foetida L) is a type of kapok plant that has been scientifically proven to have activity as an anti-inflammatory and analgesic. 70% ethanol extract of stem stem is obtained by maceration using 70% ethanol. Examination of the characteristics of 70% ethanol extract of kepuh stem included organoleptic, of moisture content and determination of residual solvent content. Phytochemical screening of 70% ethanol extract of kepuh bark includes: alkaloid, flavonoid, saponin, tannin , polyphenol, and examination of glycosides. The results of the examination of the characteristics of 70% ethanol extract of kepuh stem obtained water content of 8.66 ± 0.748%, the residual content of the solvent had a 0 (zero) ethanol level. The results of phytochemical screening showed 70% ethanol extract of stem stem containing steroid compounds, triterpenoids, flavonoids, saponins, tannins and polyphenols. The identification using UV-Vis spectrophotometry produced ? 212, the absorbance was 1.8601 and ? 284, the absorbance was 0.42186.